Study on Pyrazolo-4-carboxaldehyde: Synthesis of Fused Pyrazole, Isoxazole, Pyrimidine and Pyridine-[2, 3-d]-Pyrazoline Derivatives - Abd El Latif, F.M. (Asian Journal of Chemistry, 2010)
4-Carboxaldehyde-5-chloro-3-methyl-1-phenylpyrazoline has been used to synthesize several heterocyclic compounds via condensation substitution, elimination and cycloaddition reactions.